THE MYTH OF HOMECOMING in THE FILM PURANG BY AZHAR KINOI LUBIS A STUDY OF ROLAND BARTHES' SEMOTICS - Mufti Isror Alfarobby; Ririe Rengganis (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2023)
ABSTRACT The film that will be studied in this research is "Pulang" by Azhar Kinoi Lubis. The film, produced by KlikFilm Productions, RK23 and Canary studios, premiered on April 2, 2022. Carrying the genre of Indonesian family drama. The analysis in this study was conducted to describe the symbols in the film Pulang and identify the form of meaning contained in it, starting from the meaning of denotation, connotation and myth. The method used in this research is Content Analysis using Rolan Barthes' semiotic analysis theory. This study uses descriptive qualitative research to solve 3 main problems, including: (1) identifying the meaning of denotation, (2) identifying the meaning of connotation, (3) outlining the meaning of myth in the cinema entitled Pulang by director Azhar Kinoi Lubis. This research concludes that the denotative meaning in this film is about the amount of love that parents have for their children, the connotative meaning of each conflict that arises as a result of their respective egos, and the myth of going home to hometown is not only about going home to celebrate a meeting, but also about going home to celebrate a meeting. Keywords: film, semiotic, connotation, denotation, myth